Seasonal mercury concentrations and δ15N and δ13C values of benthic macroinvertebrates and sediments from a historically polluted estuary in south central Chile - Diaz Jaramillo, Mauricio Javier (2013)
The Lenga Estuary is one of the most industrialized sites in south central Chile where the historic operation of chlor-alkali plants resulted in large quantities of mercury (Hg) being deposited into the estuary. This historical contamination may still represent a risk to the biota in the estuary. To investigate this four macroinvertebrates, Neotrypaea uncinata (ghostshrimp), Elminius kingii (barnacle), Hemigrapsus crenulatus (shore crab) and Perinereis gualpensis (ragworm) were collected seasonally from three different sites in the Lenga Estuary and one in a reference estuary (Tubul Estuary), and analyzed for Hg and stable isotopes (δ15N and δ13C). Mercury concentrations in Lenga sediments ranged from 0.4 ± 0.1 to 13 ± 3 mg/kg, while those in Tubul sediments ranged from 0.02 ± 0.01 to 0.07 ± 0.09 mg/kg. Total Hg concentrations of invertebrates were significantly different between estuaries (p < 0.05), but not by species or season for each estuary (p > 0.05). In contrast, organic Hg concentrations were different by species and season with shore crab muscle tissues exhibiting the greatest percent difference. Site-specific relationships demonstrated that total Hg concentrations in ragworm best reflected the total Hg sediment mercury concentrations. Signatures of δ13C were correlated to the organic Hg % rather than total Hg. This suggests that organic Hg concentrations in these species were related to the carbon sources.